The vespertine - Mitchell, Saundra (Harcourt, 2011)
It's the summer of 1889, and Amelia van den Broek is new to Baltimore. Her gaiety is interrupted by disturbing, dreamlike visions that offer glimpses of the future. When one of her darkest visions comes to pass, Amelia's world is thrown into chaos.